Can NFL Combine results be used to estimate NFL defensive players longevity? - Pollock, J. R.; Doan, M. K.; Asprey, W. L.; Dulle, D. L.; Moore, W. L.; Makovicka, J. L.; Hassebrock, J. D.; Foley, B. M.; Chhabra, A. (Sports Medicine International Open, 2021)
The National Football League Scouting Combine is an annual event held to evaluate football players. The results of the combine are used to identify talent and player potential. Our study aims to examine the relationship between combine drill performance (e.g., speed, power, agility, explosiveness) and career longevity. We performed a retrospective review of The National Football League combine test results for all defensive players from 2005-2015 to determine the association of each player`s combine test results with career longevity. The position that had the most significant associations for 1-year status was linebackers, with weight, 10-yard dash, 20-yard dash, 40-yard dash, broad jump, 3-cone drill, and shuttle being significantly associated with 1-year roster status. The position that had the most significant associations for 5-year status was cornerbacks, with weight, 10-yard dash, 20-yard dash, 40-yard dash, 3-cone drill, and shuttle being significantly associated with 1-year roster status. The least number of significant associations was found for safeties, with no drill being associated with 1-year roster status and only height and shuttle time significantly associated with 5-year career longevity. Our study demonstrates the utility of the combine results to help estimate the career longevity of NFL defensive players.